Anticancer Activity and Apoptosis Induction of Alkaloid Fraction of Kratom Leaves (Mitragyna speciosa) on Breast Cancer Cells: In Vitro and In Silico Studies - Adi Priatna, Puja; Rahmah, Siti; Widyowati, Retno; Sukardiman, Sukardiman (Trends in Sciences, 2025)
Breast cancer is one of the highest causes of death in women. However, cancer therapy drugs have weaknesses, low selectivity, which results in reduced efficacy. Kratom contains alkaloid group compounds that have a cytotoxic effect. This study aimed to evaluate the cytotoxic effects and apoptosis mechanisms on the alkaloid fraction of Kratom Leaves. Additionally, identify their metabolite with LC-MS/MS and molecular docking to predict its apoptotic activity. Fractionation was carried out by liquid-liquid extraction and acid-base methods. The cytotoxic test was carried out using the MTT assay method on extract and alkaloid fractions on T47D breast cancer cells. Apoptosis mechanism testing was performed using AO/EB staining. Identification of the chemical composition of alkaloid fractions with LC-MS/MS as a ligand to perform molecular docking. The proteins used as molecular docking targets are the 3ERT protein (estrogen receptor) and the 2W3L protein (Bcl-2 receptor). The alkaloid fraction of kratom leaves can provide moderate cytotoxic activity with an IC50 of 96.23 µg/mL against T47D cells compared to kratom leaf extract, which has weak potential with an IC50 value of 419.21 µg/mL. Research finds that the alkaloid fraction of kratom leaves exhibits superior cytotoxic activity in T47D cells compared to kratom leaf extract samples. The alkaloid component significantly promoted apoptotic induction compared with untreated control cells. The alkaloid fraction was found to contain 8 alkaloid compounds: 7-Hydroxymitragynine, Corynantheidine, Isorhynchophylline, Mitragynine, Pholcodine, Polyneuridinealdehyde, Rotundifolone, and Yohimbine. Moreover, polyneuridinealdehyde exhibits the greatest potential in silico against estrogen receptors, while yohimbine demonstrates significant efficacy against Bcl-2 receptors. HIGHLIGHTS The alkaloid fraction of kratom leaves can provide cytotoxic activity against T47D breast cancer cells. The alkaloid fraction of kratom leaves shows superior cytotoxic activity and can induce apoptosis in T47D breast cancer cells. The active alkaloid fraction of kratom leaves contains 8 compounds, including 7-hydroxymitragynine, corynantheidine, isorhynchophylline, mitragynine, pholcodine, polyneuridinealdehyde, rotundifolone, and yohimbine. Polyneuridinealdehyde shows the greatest potential in silico against estrogen receptors, while yohimbine shows significant efficacy against Bcl-2 receptors. GRAPHICAL ABSTRACT